Alicia Alonso : prima ballerina - Bernier-Grand, Carmen T. (Two Lions, 2011)
Presents the biography and special achievements of Alicia Alonso who, despite being partially blind, became the Cuban prima ballerina and choreographer extraordinaire. Demonstrates her drive and dedication to her art and provides a chronology of events during her career.